Non-catalytic pyrolysis of ethane to ethylene in the presence of CO2 with or without limited O-2 - Choudhary, Vasant R.; Mondal, Kartick C.; Mulla, Shafeek Abdul Rashid (Journal of Chemical Science, 2006)
Influence of the presence Of CO2, which is a mild oxidant, on the performance of the thermal cracking of ethane to ethylene in the absence or presence of limited O-2 at different temperatures (750-900 degrees C), space velocities (1500-9000 h(-1)) and CO2/C2H6 and O-2/C2H6 mole ratios (0-2.0 and 0-0.3 respectively) has been investigated. In both the presence and absence of limited 02, ethane conversion increases markedly because of the presence Of CO2, indicating its beneficial effect on the ethane to ethylene cracking. The increased ethane conversion is, however, not due to the oxidation of ethane to ethylene by CO2; the formation of carbon monoxide in the presence Of CO2 is found to be very small. It is most probably due to the activation of ethane in the presence Of CO2.
Keywords: ethane; ethane cracking in presence Of CO2; ethane cracking in presence of CO2 and limited O-2; Ethylene; thermal cracking of ethane

Photodegradation of ethylene/propylene/polar monomers, Co-, and terpolymers. II. prepared by Ni catalyst systems - Fernandes, Susete N.; Correia, Sandra; Matos, Ines; Marques, Maria M.; Rana, Sravendra; Kumar, Bijandra; Gupta, M. K.; Singh, R. P. (Journal of Applied Polymer Science, 2007)
The copolymers of ethylene/propylene as well as their terpolymers with polar monomers were prepared by Ni-catalyst systems and their photodegradation behavior was studied by Fourier transform infrared spectroscopy. The polar monomers used to synthesize co- and terpolymers of ethylene/propylene/polar monomer were 5-hexen-1-ol, 10-undecen-1-ol, acrylamide, methylmethacrylate, acrylonitrile, and methylvinyl ketone. The morphological changes of the irradiated samples were determined by scanning electron microscopy. The photodegradation kinetics has also been studied. The surface damage caused by polychromatic irradiation (lambda >= 290 nm) at 55 degrees C in atmospheric air is presented in different micrographs. The rate of photo-oxidative degradation is very fast in terpolymers containing polar monomers as compared with copolymers and homopolymers. The morphological study of the photodegraded samples showed a very good correlation with the photodegraded results. (c) 2007 Wiley Periodicals, Inc.
Keywords: copolymerization; Ethylene; Photodegradation; polar monomers; propylene

Selective oxidation of ethane over Mo-V-Al-O oxide catalysts: insight to the factors affecting the selectivity of ethylene and acetic acid and structure-activity correlation studies - Sankaranarayanan, T. M.; Ingle, Rohit H.; Gaikwad, T. B.; Lokhande, S. K.; Raja, T.; Devi, R. N.; Ramaswamy, V.; Manikandan, Palanichamy (Catalysis Letters, 2008)
Catalysts of general formula, MoVAlOx were prepared with the initial elemental composition of 1:0.34:0.167 (Mo:V:Al) at a pH value in the range of 1-4. The elemental analysis showed that the final composition of the catalysts is pH dependant. The performance of the catalysts was tested for selective oxidation of ethane to give ethylene and acetic acid. While all of them were active for ethane oxidation with a moderate conversion, the catalyst prepared at pH 2 showed a highest activity with 23% ethane conversion and a combined selectivity of 80.6% to ethylene and acetic acid. The catalyst prepared at pH 4 was least selective to ethylene and acetic acid. Various techniques like powder XRD, SEM, Raman, UV-Vis and EPR were used to characterize the catalysts and to identify the active phases responsible for the selective oxidation of ethane. The powder XRD data showed that the catalysts prepared at pH 1 and 2 contain mainly of MoO3 and MoV2O8 along with traces of Mo4O11. The amount of MoO3 was slightly higher in the catalyst prepared at pH 1. However, the catalyst prepared at pH 3 contains mainly of MoV2O8 with no trace of MoO3. The catalyst prepared at pH 4 showed V2O5 as the major phase along with MoVAlO4 phase. The Raman data corroborated the XRD results. EPR and UV-Vis studies indicated the presence of traces of V-4 in pH 1 and 2 catalysts and significant amount of Mo5+ in all the catalysts. Thus, the high activity and selectivity to ethylene and acetic acid are attributed to the presence of MoV2O8 phase and other reduced species like Mo4O11 phase supported on MoO3. The presence of V and Mo ions in a partially reduced form seems to play a crucial role in the selective oxidation of ethane.
Keywords: Acetic acid; ethane; Ethylene; mixed metal oxide; Selective oxidation

Heteropolyacid supported on montmorillonite catalyst for dehydration of dilute bio-ethanol - Bokade, Vijay V.; Yadav, Ganapati D. (Applied Clay Science, 2011)
Vapour phase dehydration of dilute bio-ethanol (EtOH) to ethylene (E) and diethyl ether (DEE) is industrially relevant. Ethylene is an important raw material for many petrochemical products and Diethyl ether (DEE) can be used as an alternative fuel. The efficacy of montmorillonite (K-10) and dodecatungestophosphoric acid (DTPA) supported on montmorillonite (DTPA/K-10), has been evaluated in the current work in the dehydration of dilute bio-ethanol (80%m/m). The dehydration of ethanol and cracking of diethyl ether were studied independently. 30% m/m DTPA/K-10 was found to be more active with 74% ethanol conversion and 92% ethylene selectivity at 250 degrees C in comparison with other acid catalysts used. The merit of the process lies in its use of dilute bio-ethanol, a new avenue for ethylene production from a non-petroleum feedstock. Kinetic interpretation has been made by studying the important process parameters by using 30%m/m DTPA/montmorillonite as the catalyst. The mechanism of the dehydration of ethanol reaction suggests that two types of sites are responsible. The dehydration of ethanol and cracking of diethyl ether are second order reactions with weak adsorption of species. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Bio-ethanol; dehydration; Diethyl ether; Ethylene; Heteropolyacid

Spatial and temporal changes in the volatile profile of alphonso mango upon exogenous ethylene treatment - Chidley, Hemangi G.; Kulkarni, Ram S.; Pujari, Keshav H.; Giri, Ashok P.; Gupta, Vidya S. (Food Chemistry, 2013)
Alphonso is a highly favoured and exported mango cultivar among the vast mango germplasm of India. Being a climacteric fruit, ethylene plays an important role in ripening of mango. For deeper understanding of effect of pre-climacteric ethylene treatment on volatile profiles of Alphonso mango, 26 volatiles were tracked through six ripening stages of pulp and skin of ethylene-treated and control Alphonso fruits. The study revealed accelerated ripening in terms of early appearance of ripening-specific compounds, lactones and mesifuran, upon ethylene treatment. While the level of lactones remained unaffected, the mesifuran level vastly increased upon ethylene treatment. Skin showed high terpene content while pulp had higher amount of lactones compared to skin. This work points towards involvement of ethylene as a natural hormone in the biosynthesis of lactones and furanones in naturally ripened fruits; whereas, an increase in the terpene level during ripening appears to be independent of ethylene. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Ethylene; Flavour; Mango; Pre-climacteric; Ripening; Volatiles

Molecular cloning and characterization of O-methyltransferase from mango fruit (mangifera indica cv. alphonso) - Chidley, Hemangi G.; Oak, Pranjali S.; Deshpande, Ashish B.; Pujari, Keshav H.; Giri, Ashok P.; Gupta, Vidya S. (Molecular Biotechnology, 2016)
Flavour of ripe Alphonso mango is invariably dominated by the de novo appearance of lactones and furanones during ripening. Of these, furanones comprising furaneol (4-hydroxy-2,5-dimethyl-3(2H)-furanone) and mesifuran (2,5-dimethyl-4-methoxy-3(2H)-furanone) are of particular importance due to their sweet, fruity caramel-like flavour characters and low odour detection thresholds. We isolated a 1056 bp complete open reading frame of a cDNA encoding S-adenosyl-l-methionine-dependent O-methyltransferase from Alphonso mango. The recombinantly expressed enzyme, MiOMTS showed substrate specificity towards furaneol and protocatechuic aldehyde synthesizing mesifuran and vanillin, respectively, in an in vitro assay reaction. A semi-quantitative PCR analysis showed fruit-specific expression of MiOMTS transcripts. Quantitative real-time PCR displayed ripening-related expression pattern of MiOMTS in both pulp and skin of Alphonso mango. Also, early and significantly enhanced accumulation of its transcripts was detected in pulp and skin of ethylene-treated fruits. Ripening-related and fruit-specific expression profile of MiOMTS and substrate specificity towards furaneol is a suggestive of its involvement in the synthesis of mesifuran in Alphonso mango. Moreover, a significant trigger in the expression of MiOMTS transcripts in ethylene-treated fruits point towards the transcriptional regulation of mesifuran biosynthesis by ethylene.
Keywords: Ethylene; expression; Flavour; Mango; Mesifuran; Ripening

Methanol-to-light olefins reaction using Zn-Ag modified SSZ-13 catalyst - Dange, Rutvija M.; Gawali, Chirag B.; Niphadkar, Prashant S.; Bokade, Vijay V.; Nandanwar, Sachin U. (ChemistrySelect, 2022)
The 2 wt.% of Zn and Ag (Zn1-x-Ag-x; x=0.2, 0.4, 0.6 %) modified SSZ-13 (SZ-13) zeolite was prepared by wet-impregnation method, and its catalytic activity was demonstrated for methanol-to-olefin (MTO). The Zn-0.6-Ag-0.4/SZ-13 catalyst exhibited high catalytic activity due to change in properties of catalyst. The Zn particles were highly dispersed inside the SZ-13; while Ag particles were dispersed on the surface of SZ-13, confirmed by HRTEM and surface area. The small % of Ag over SZ-13 promotes ethylene production via aromatization of reaction, and highly dispersed Zn on SZ-13 help to produce stable ethylene and propylene. The Zn-0.6-Ag-0.4/SZ-13 catalyst showed (similar to 10 %) higher light olefin (87 %) selectivity than parent SZ-13 as well as mono metal incorporated SZ-13. The higher catalytic activity was attributed due to effect of both metals (Zn and Ag), where Ag promotes partial aromatization on the surface, and Zn increases the Lewis acidity in the zeolite pore. This catalyst can help to improve the selectivity of light olefin using MTO reaction.
Keywords: Ethylene; Methanol-to-Olef; Propyl; Silver; SSZ; zinc